The immunomodulatory effects of mesenchymal stem cell-derived extracellular vesicles in Alzheimer's disease - Ye, Yang; Gao, Mingzhu; Shi, Wentao; Gao, Yan; Li, Yilu; Yang, Wenhui; Zheng, Xiaomin; Lu, Xiaojie (Frontiers in Immunology, 2024)
Neuroinflammation has been identified as another significant pathogenic factor in Alzheimer's disease following Aβ amyloid deposition and tau protein hyperphosphorylation, activated in the central nervous system by glial cells in response to injury-related and pathogen-related molecular patterns. Moderate glial cell activity can be neuroprotective; however, excessive glial cell activation advances the pathology of Alzheimer's disease and is accompanied by structural changes in the brain interface, with peripheral immune cells entering the brain through the blood-brain barrier, creating a vicious circle. The immunomodulatory properties of mesenchymal stem cells (MSCs) are primarily conveyed through extracellular vesicles (EVs). MSC-EVs participate in chronic inflammatory and immune processes by transferring nucleic acids, proteins and lipids from the parent cell to the recipient cell, thus MSC-EVs retain their immunomodulatory capacity while avoiding the safety issues associated with living cell therapy, making them a promising focus for immunomodulatory therapy. In this review, we discuss the modulatory effects of MSC-EVs on Alzheimer's disease-associated immune cells and the mechanisms involved in their treatment of the condition. We have found a clinical trial of MSC-EVs in Alzheimer's disease treatment and outlined the challenges of this approach. Overall, MSC-EVs have the potential to provide a safe and effective treatment option for Alzheimer's disease by targeting neuroinflammation.